Research on moving load identification based on measured acceleration and strain signals. (19th November 2019) - Zhou, Yun; Zhou, Sai; Deng, Lu; Chen, Songbai; Yi, Weijian
Moving load identification from the dynamic responses of bridges is a typical inverse problem that is solved to estimate vehicle axle loads in motion from observed data. To reduce the ill-posedness of the problem and improve solution accuracy, this paper proposes a method for reconstructing the dynamic displacement response via combining the measured acceleration and strain signals for moving load identification. The identification accuracy achieved by employing the reconstructed displacement under different vehicle speeds and different identification algorithms was investigated via finite element (FE) analysis, and a laboratory experiment of a simply supported beam model was constructed to validate the effectiveness of the proposed method. Both the computation simulations and experimental results indicate that the reconstructed displacements fit the true values well and the proposed method can effectively overcome the ill-posedness of the problem in terms of equation resolution and achieve a high level of accuracy.